2019
DOI: 10.3389/fphar.2019.01325
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ayahuasca on Suicidality: Results From a Randomized Controlled Trial

Abstract: Suicide is a major public health problem. Given increasing suicide rates and limitations surrounding current interventions, there is an urgent need for innovative interventions for suicidality. Although ayahuasca has been shown to target mental health concerns associated with suicidality (i.e., depression and hopelessness), research has not yet explored the impact of ayahuasca on suicidality. Therefore, we conducted secondary analyses of a randomized placebo-controlled trial in which individuals with treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 81 publications
(111 reference statements)
1
45
0
5
Order By: Relevance
“…Importantly, we did not find significant increases in depression severity or suicidal ideation from 2-weeks to 4-weeks, suggesting that the positive effects of psychedelics were reliably sustained for at least 1-month post-psychedelic use. These results are in line with clinical studies indicating that psychedelics can lead to decreases in depression severity [e.g., ( 13 , 14 )] and suicidal ideation ( 13 , 15 ) and that these effects are sustained over time [e.g., ( 4 , 6 , 13 )]. Importantly, in both studies, the majority of the participants (Study 1 = 72.2%; Study 2 = 81.9%) exhibited subclinical levels of baseline depression severity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Importantly, we did not find significant increases in depression severity or suicidal ideation from 2-weeks to 4-weeks, suggesting that the positive effects of psychedelics were reliably sustained for at least 1-month post-psychedelic use. These results are in line with clinical studies indicating that psychedelics can lead to decreases in depression severity [e.g., ( 13 , 14 )] and suicidal ideation ( 13 , 15 ) and that these effects are sustained over time [e.g., ( 4 , 6 , 13 )]. Importantly, in both studies, the majority of the participants (Study 1 = 72.2%; Study 2 = 81.9%) exhibited subclinical levels of baseline depression severity.…”
Section: Discussionsupporting
confidence: 89%
“…Now I know how to deal with my feelings rather than repress them" (1) Serotonergic psychedelics, a class of pharmacological agents that act as serotonin 2A receptor (5-HT2AR) agonists, including psilocybin, lysergic acid diethylamide (LSD), and dimethyltryptamine (DMT; contained in the brew ayahuasca), are currently receiving attention within psychiatry and mental health as novel interventions for a wide range of mental health concerns [for reviews, see (2,3)]. Randomized controlled trials and open-label trials have found promising results for psychedelic therapy in the treatment of distress associated with a life-threatening illness [e.g., (4)(5)(6)], substance use disorders [e.g., (7)(8)(9)(10)], obsessive-compulsive disorder (11), depression [e.g., (12)(13)(14)], and suicidal ideation (13,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayahuasca is an Amazonian brew made with Psychotria viridis , a rubacea containing N, N-DMT, and Banisteriopsis caapi , a vine which contains β-carbolines that are reversible inhibitors of monoamine oxidase and an inhibitor of serotonin reuptake (Palhano-Fontes et al 2014 ). This psychedelic also has been subject to increasing research, which has included effects on mood and addiction in healthy volunteers (McKenna 2004 ; Riba et al 2001 ; Santos et al 2007 ; Uthaug et al 2018 ), as well as clinical trials investigating its psychological and neurobiological antidepressant effects in open-label and double-blind designs (de Almeida et al 2019 ; Dos Santos et al 2011 ; Galvão et al 2018 ; Osorio Fde et al 2015 ; Palhano-Fontes et al 2019 ; Zeifman et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 24 Furthermore, an open-label 25 and a placebo-controlled trial 26 showed that ayahuasca administration reduced depression, anxiety, and suicidality in patients with TRD. 27 , 28 …”
Section: Introductionmentioning
confidence: 99%